Structural fatigue reliability evaluation based on probability analysis of the number of zero-crossings of stochastic response process. (January 2023) - Zhang, Zhenhao; Zhao, Chengwei; Zhao, Zhenpeng; Wang, Fuming; Zhao, Bing
Highlights: Functional relationship between stress cycles number and fatigue cumulative damage is derived. Distribution law of the number of intersections between Wiener process and zero-boundary is obtained. Random fatigue failure analysis method based on the number of zero-crossing of stochastic process is proposed. A practical example is employed for the fatigue reliability assessment of Metro Bogie. Abstract: Structural fatigue failure is closely related to the number of stress cycles. Therefore, the number of the intersections between stochastic response process and zero-boundary is a key problem in structural fatigue reliability analysis. In this paper, the relationship between the number of the multiple intersections and the fatigue cumulative damage index is derived according to the Miner rule-based high cycle fatigue random cumulative damage index. Then, use random walk to approximately simulate Wiener process, and get the first intersection probability between Wiener process and the zero-boundary. Next, further utilize the renewal process to solve the distribution law of the number of intersections between the Wiener process and the zero-boundary in a period of time. Finally, based on the fatigue failure criterion considering the randomness of the failure threshold, the calculation formula the structural fatigue reliability is derived. As a practical example, the fatigue reliabilities of the key part of Metro Bogie under different operation periods are analyzed using the proposed method.